Políticas públicas e cidadania: qual o papel dos Correios nessa relação? - ALMEIDA, Raimunda Eunice da Silva (2015)
This paper is based on a study done at Empresa Brasileira de Correios e Telégrafos (ECT), to assess whether it is possible for ECT to continue playing the role of social agent facing the growing needs of the communities and the government, given the viability requirement in such a competitive market, in which it analyzes the Post Office in its role of social integrator as a support tool for public policies to promote citizenship, as an agent of the federal public service and holder of a service network present in all municipalities of the country. It sought the identification of the changes that the post office is encountering due to technological and social advances, through the survey of the services offered, the structure and implemented social projects, mapping of the main changes in society, through the analysis of secondary data, evaluation of the postal traffic behavior messages and orders, the consequences for the survival of traditional segments and influence the formulation of policies, strategies and actions of the Company, and the demonstration of the role of the Post Office as a social integrator, through study case of ECT, with reference to the period from 2001 to 2013. It presents initially a brief conceptualization of the core issues, the study objects, followed by a diagnosis and their analyzes of the ECT, the Postal Industry and the use of the Post Office as a support tool for the implementation of government projects and actions. Following it is showed the history of services already provided by the Post Office, which demonstrate the promotion of integration of public policies in order to contribute actions to promote citizenship, social inclusion and accessibility for citizens. The methodology includes the collection of data and information of the posted volumes, as well as information on the postal industry, seeking to evaluate the correlations by statistical analysis. It also involves cataloging the social projects implemented for the period 2001 to 2013. The study found that new technologies are responsible for changes in postal traffic behavior of letters and parcels and the diversification of products and services can affect, even more, the portfolio of the postal sector. The study also demonstrated that the operational infrastructure and services provided by ECT may be increasingly used as tools to support public policy and citizenship.